2013
DOI: 10.12717/dr.2013.17.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fertilizing Ability using Frozen Thawed Sperm in the Longtooth Grouper, Epinephelus bruneus

Abstract: : This study examines the effects on fertilization rate (FR), hatching rate (HR), and normal individual rate after artificial fertilization using frozen thawed sperm according to the cryoprotectant (DMSO) concentration and the period of cryopreserved sperm of longtooth grouper, Epinephelus bruneus. Performing artificial fertilization using frozen-thawed sperm, after freezing the sperm at different DMSO concentration of 5.0%, 7.5%, 10.0% respectively, FR were (DMSO 5.0%: 99.5±0.8%, DMSO 7.5%: 99.5±0.7%, and DMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This may imply that none of Na + and Cl ‐ ions was a key component triggering the initiation of sperm motility of Asian seabass and may also account for such a phenomenon of Ringer's solution. This solution has been also used as an effective extender for sperm cryopreservation of red snapper, Lutjanus argentimaculatus (Vuthiphandchai, Chomphuthawach, et al., 2009), and long tooth grouper, Epinephelus bruneus (Oh et al., 2013). Other sperm extenders used in the present study were found to be highly effective to prolong sperm life of teleosts, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply that none of Na + and Cl ‐ ions was a key component triggering the initiation of sperm motility of Asian seabass and may also account for such a phenomenon of Ringer's solution. This solution has been also used as an effective extender for sperm cryopreservation of red snapper, Lutjanus argentimaculatus (Vuthiphandchai, Chomphuthawach, et al., 2009), and long tooth grouper, Epinephelus bruneus (Oh et al., 2013). Other sperm extenders used in the present study were found to be highly effective to prolong sperm life of teleosts, e.g.…”
Section: Discussionmentioning
confidence: 99%